Analysis of dynamic mechanical properties of sprayed fiber-reinforced concrete based on the energy conversion principle. (10th September 2020) - Chen, Lianjun; Zhang, Xixin; Liu, Guoming
Highlights: The SHPB test was used to study fiber-reinforced shotcrete. A comprehensive analysis of dynamic properties in shotcrete was conducted. The energy consumption ratio of fiber-reinforced concretes was determined. The corresponding formula of energy and dynamic compressive strength was established. Abstract: In order to study the dynamic mechanical properties of sprayed fiber-reinforced concrete under impact loads, a φ50mm split Hopkinson (SHPB) device was employed to perform dynamic compression experiments on sprayed plain concrete, polypropylene fiber-reinforced concrete, and plastic steel fiber-reinforced concrete. Variations in the fracture state and waveform of different sample were obtained through experimentation. The toughness, energy consumption, and strength increased with increasing of strain rate. These fibers improved the dynamic mechanical properties of shotcrete. Plastic steel fibers significantly increased the dynamic compressive strength of shotcrete, while polypropylene fibers significantly improved the toughness and energy consumption ratio. The strain rate effect and the fiber reinforcement principle were analyzed from an energy conversion perspective. A correlation analysis of the elastic strain energy change rate and the dynamic compressive strength was used to obtain a fitting curve, and showed a positive linear correlation between the two. This provides a theoretical basis for further studies on how to improve the dynamic mechanical properties of fiber-reinforced concrete from an energy conversion perspective.